Collapsin response mediator protein 4 affects the number of tyrosine hydroxylase‐immunoreactive neurons in the sexually dimorphic nucleus in female mice. Issue 7 (14th May 2013) - Iwakura, Takashi; Sakoh, Miyuki; Tsutiya, Atsuhiro; Yamashita, Naoya; Ohtani, Akiko; Tsuda, Mumeko C.; Ogawa, Sonoko; Tsukahara, Shinji; Nishihara, Masugi; Shiga, Takashi; Goshima, Yoshio; Kato, Tomohiro; et al.
<x xml:space="preserve">Abstract</x> In the sexually dimorphic anteroventral periventricular nucleus (AVPV) of the hypothalamus, females have a greater number of tyrosine hydroxylase‐immunoreactive (TH‐ir) and kisspeptin‐immunoreactive (kisspeptin‐ir) neurons than males. In this study, we used proteomics analysis and gene‐deficient mice to identify proteins that regulate the number of TH‐ir and kisspeptin‐ir neurons in the AVPV. Analysis of protein expressions in the rat AVPV on postnatal day 1 (PD1; the early phase of sex differentiation) using two‐dimensional fluorescence difference gel electrophoresis followed by MALDI‐TOF‐MS identified collapsin response mediator protein 4 (CRMP4) as a protein exhibiting sexually dimorphic expression. Interestingly, this sexually differential expressions of CRMP4 protein and mRNA in the AVPV was not detected on PD6. Prenatal testosterone exposure canceled the sexual difference in the expression of Crmp4 mRNA in the rat AVPV. Next, we used CRMP4‐knockout (CRMP4‐KO) mice to determine the in vivo function of CRMP4 in the AVPV. Crmp4 knockout did not change the number of kisspeptin‐ir neurons in the adult AVPV in either sex. However, the number of TH‐ir neurons was increased in the AVPV of adult female CRMP4‐KO mice as compared with the adult female wild‐type mice. During development, no significant difference in the number of TH‐ir neurons was detected between sexes or genotypes on embryonic day 15, but a female‐specific increase in TH‐ir neurons was observed in CRMP4‐KO mice on PD1, when the sex difference was not yet apparent in wild‐type mice. These results indicate that CRMP4 regulates the number of TH‐ir cell number in the female AVPV. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 73: 502–517, 2013